Asymmetry as a general cue for V2 (loss) - Pierre Larrivée; Cecilia Poletto; Francesco Pinzin; Mathieu Goux (Isogloss)
This paper identifies a micro-cue correlating to verb second word order (V2) in two closely related Medieval Romance languages. As V2 is asymmetrically distributed in main rather than subordinate clauses, an asymmetry would be expected in phenomena assumed to relate to V2, such as subject inversion, null subject and enclisis. The loss of that asymmetry should therefore indicate the loss of the V2 word order rule. These assumptions are tested here by a quantitative analysis of a treebank of calibrated data covering the crucial period of change (from the 14th to the 16th century) for Medieval French and Venetian. The hard quantitative evidence provided demonstrates that the main versus embedded asymmetry is indeed a micro-cue of V2 structure, and of its loss in one of the two investigated languages.